2021
DOI: 10.1177/10497315211042096
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Adventure-based Cognitive Behavioral Program for Hong Kong University Students

Abstract: Objectives: This pilot study developed an adventure-based cognitive behavioral intervention (aCBI) program and tests its effectiveness in improving the mental health of Chinese university students in Hong Kong. Method: A total of 217 undergraduate students participated in an aCBI program in the form of an interdisciplinary general education course in a university in Hong Kong. A battery of standardized online questionnaires was administered to the students before joining and upon completion of the course, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…Health authorities should provide public health education, implement psychological health services online and offline [ 75 ], integrate cognitive behavioral intervention and adventure training in a class setting [ 78 ], and offer mental health services reducing posttraumatic stress disorder [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Health authorities should provide public health education, implement psychological health services online and offline [ 75 ], integrate cognitive behavioral intervention and adventure training in a class setting [ 78 ], and offer mental health services reducing posttraumatic stress disorder [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study advances a pilot study (Pan & Zhuang, 2022) to further determine the effectiveness of aCBI on university students through a more rigorous RCT research design. The findings confirm the positive effects of aCBI on improving various mental health outcomes of university students.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…The third component was adventure-based activities. A pilot study of the aCBI model has yielded promising results based on a pre-post quasi-experimental design (Pan & Zhuang, 2022) conducted with 217 undergraduate students in Hong Kong and found that the participants showed a significant reduction of psychological distress, depressive symptoms, and negative thoughts and emotions, and a significant increase of positive thoughts upon immediate completion of the program. The positive effects were sustained at the 3-month follow-up test.…”
Section: Current Studymentioning
confidence: 99%
“…The functions of the program include: (1) 8 online modules, which focus on a variety of cognitive behavioral skills to cope with university stress. The contents are developed based on CBT in Beck (2011) and Wong (2005) for Chinese clients, and the CBT work for Chinese university students ( Pan and Zhuang, 2022 ). The skillsets include cognitive skills such as self-talk, building evidence for and against, advantage and disadvantage analyses, pie chart and cognitive continuum, and behavioral skills such as behavioral experiment and behavioral activation.…”
Section: Methodsmentioning
confidence: 99%